Aggressive Teenagers Behaviour as Factor of Victimization - Papusha, Vladislav Vyacheslavovich (Psychological Prospects Journal, 2012)
The teenagers aggressive behaviour aspects as factor of the victimization, are exposed in the article. Teenagers’ aggression provoking violence is considered.
Keywords: aggression victim behaviour factors of victimization violence